ANALYSIS STRUCTURE OF EPILITHIC DIATOMS COMMUNITY IN COASTAL WATERS OF DUMAI RIAU PROVINCE - Gustini Sri Ulina; Sofyan H. Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in June 2015 in the coastal waters of Dumai RiauProvince. This study observed the variety, abundance and community structure ofepilithic diatoms contained in coastal waters and to inform about the ecology of aquaticenvironment. The epilithic diatoms sample were collected in the field and identified inthe Marine Biological Laboratory of Marine Science Department, Faculty of Fisheriesand Marine Sciences, University of Riau. The number of genus recorded were 8 genera,namely Cymatopleura, Dactyliosolen, Leptocylindrus, Nitzschia, Rhabdonema,Rhizosolenia, Thallassiothrix and Triceratium. Epilithic diatoms genus found in eachstation was Rhabdonema. The genus can be bound or attached to rocks because it has acosmopolitan nature in which not susceptible to flow. The values of diversity index (H'), dominance (D) and diversity (E) indicated that the condition of coastal waters Dumaiunder pressure and moderate pollution levels, no diatoms dominated, uniformitybalanced and no competition of food and places. Based on the calculation of theabundance of diatom ANOVA test did not differ significantly between stations.Keywords: coastal waters, Dumai, diatoms, epilithic